2017
DOI: 10.1590/s1679-45082017ao3888
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability based on risk stratification for type 2 diabetes mellitus

Abstract: Objective To evaluate heart rate variability among adults with different risk levels for type 2 diabetes mellitus.Methods The risk for type 2 diabetes mellitus was assessed in 130 participants (89 females) based on the questionnaire Finnish Diabetes Risk Score and was classified as low risk (n=26), slightly elevated risk (n=41), moderate risk (n=27) and high risk (n=32). To measure heart rate variability, a heart-rate monitor Polar S810i® was employed to obtain RR series for each individual, at rest, for 5 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…These findings thus collectively imply that the impairment of vagus functional status appears early in the disease course of DM [27]. Silva et al [28] found that lower HRV value was a risk factor for worse outcome among DM patients. Our results showed that sympathetic dysfunction is more significant in DM patients with higher HbA1c level.…”
Section: Discussionmentioning
confidence: 79%
“…These findings thus collectively imply that the impairment of vagus functional status appears early in the disease course of DM [27]. Silva et al [28] found that lower HRV value was a risk factor for worse outcome among DM patients. Our results showed that sympathetic dysfunction is more significant in DM patients with higher HbA1c level.…”
Section: Discussionmentioning
confidence: 79%
“…35,36 Yet, many other studies associate DM with the appearance of complications in the cardiovascular system. [37][38][39] Therefore, DM is a potential predictor, knowing that it may cause impairment of the vascular system walls, in addition to carrying other clinical factors such as obesity, physical inactivity, and dyslipidemia. 40,41 The overall diabetic population is denoted at high cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that serum level of cystatin C was higher in DM patients with grade III hypertension than in patients with grade I or II, indicating that serum cystatin C level is correlated with hypertension. Silva-E-Oliveira et al ( 23 ) found that level of serum cystatin C is correlated with the flow-mediated vasodilation. Bhavsar et al ( 24 ) also found that serum cystatin C in patients with pregnancy-induced hypertension syndrome was significantly higher than that in normal control group.…”
Section: Discussionmentioning
confidence: 99%